Mastering data mining : - Berry, Michael J. A. (John Wiley & Sons, 2000)
The book offers a case study-based guide to best practices in commercial data mining. After providing the fundamental principles of data mining and customer relationship management, the authors of this book share the lessons they have learned trough a series of warts-and-all case studies drawn from their experience in a variety of industries, including e-commerce, banking, cataloging, retailling, and telecommunications.